Activity of Cellulolytic Bacteria Origin From Sediment of Mangrove Forest Ecotourism Pesawaran Lampung - Chusniasih, Dewi; Handayani, Catie; Istiadi, Khaerunissa Anbar (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2024)
Cellulolytic bacteria can hydrolyze substrates containing cellulose such as mangrove litter trapped in mangrove sediment by producing cellulase enzymes to break down cellulose into simpler compounds. The purpose of this study is to obtain bacterial isolates from mangrove sediment that have the ability to produce cellulase enzymes and to determine the activity of the cellulase enzymes they produce in degrading cellulose substrates. The methods used in this study include isolation of cellulolytic bacteria from mangrove sediments, qualitative enzyme activity test, standard curve of bacterial growth, bacterial growth curve for 24 hours, standard glucose curve, and quantitative enzyme activity test using a spectrophotometer. From the isolation results obtained 18 candidate cellulolytic bacteria with different macroscopic and microscopic characteristics. Based on the results of the qualitative enzyme test for 4 days on Zobell media added with 0.5% CMC, enzyme activity index was obtained from 5 isolates. The highest activity index of isolate M2 was on day 3 that was 1.96, isolate M3 had the highest activity index on day 4 that was 4.29, isolate M4 was 2.02 on day 4, isolate M6 was 4.39 on day 4, and isolate M13 was 3.87 on day 4. Furthermore, 3 potential iso-lates were selected based on the highest average index of enzyme activity for quantitative tests. The quantitative test results from the crude extract of the cellulase enzyme for 7 days on 0.5% CMC substrate showed that the highest hydrolysis activity occurred on day 5 by isolate M6, that was 0.151 U/mL. The other two cellulolytic isolates, isolate M3 and isolate M13, had the highest cellulose hydrolysis activity, 0.129 U/mL and 0.137 U/mL.